Developing A Maslahah-Based Model Of Islamic Social Entrepreneurship Through Impact Investment: An Al-Ghazali Perspective - Sifwatir Rif'ah; Muhammad Lathoif Ghozali (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
This study aims to analyze Islamic Social Entrepreneurship (ISE) and impact investment from the perspective of Al-Ghazali’s maslahah and to develop a conceptual model for sustainable economic development. This research employs a qualitative approach using a systematic literature review of Scopus and Sinta-indexed journals from 2020–2025. The findings reveal that ISE and impact investment are inherently aligned with Islamic economic principles, emphasizing a balance between financial returns and social impact. From Al-Ghazali’s perspective, economic activities should be oriented toward maslahah, encompassing justice, social welfare, and public benefit. This study proposes a novel conceptual model integrating Islamic social finance and impact investment within a maslahah-based framework, consisting of input, process, and output components. The model offers a value-based approach to fostering inclusive and sustainable economic development.